Comparative in vitro antimicrobial and phytochemical evaluation of methanolic extract of root, stem and leaf of Jatropha curcas linn - Sharma A.K.; Gangwar M.; Tilak R.; Nath G.; Sinha A.S.K.; Tripathi Y.B.; Kumar D. (My University, 2025)
Background: Earlier researchers have reported antibacterial activity of different specific parts, but none of the reports show the comparative microbial and phytochemical studies of root, stem and leaf extract. Objective: To compare and investigate antimicrobial, qualitative phytochemical studies, phenol, flavonoid and TLC analysis of root, stem bark, leaf extracts of Jatropha curcas Linn family Euphorbiaceae. Methods: The dried plant powder was subjected to Soxhlet extraction with methanol. These solvent extracts were subjected to a preliminary phytochemical screening to detect the different chemical principles present viz., carbohydrates, proteins, amino acids, steroids, glycosides, alkaloids, flavonoids, tannins and phenolic compounds, fixed oils. Antimicrobial activity was evaluated by disc diffusion method and minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), minimum fungicidal concentration (MFC) was calculated by micro dilution method. Thin layer chromatography was also performed using solvent system chloroform, benzene, hexane, and ethyl acetate for the analysis of a number of constituents in the plant extract. The content of the total phenolics in the extract was determined spectrometrically according to the Folin-Ciocalteu procedure and calculated as catechol equivalent. The content of total flavonoids in the extract was determined and calculated as quercetin equivalent. Result: These extracts showed antibacterial, antifungal activities against gram-positive and gramnegative bacteria with varying magnitudes. The phytochemical analysis showed the presence of alkaloid, saponin, tanins, terpenoids, steroids, glycosides, phenols and flavonoids. Maximum phenolic content (38.8) was found in leaf extract and flavonoid content (18.14) in latex of plant. Discussion: It is concluded that the antimicrobial activity showed by the plant was due to the presence of these phytochemicals. Further studies are highly needed for drug development.